2008
DOI: 10.1111/j.1365-2621.2007.01617.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and functional properties of raw and electron beam‐irradiated Mucuna pruriens seeds

Abstract: The proximate, nutritional and functional properties of raw and electron beam-irradiated (0-30 kGy) Mucuna seeds were investigated. Irradiation increased crude protein and crude carbohydrates significantly than crude lipid, crude fibre and energy. Raw seeds were rich in minerals and were not affected by irradiation except for magnesium and phosphorus. Amino acids of raw seeds were comparable to soyabean and FAO ⁄ WHO reference pattern and except for 30 kGy, no significant changes were seen in amino acid profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 77 publications
5
44
3
Order By: Relevance
“…Determining WAC is important as it assists in the formulation of various food products such as bread and soups (Oshodi and Adeladun, 1993;Bhat et al, 2008). Results obtained for the WAC and OAC for the different rice varieties evaluated in the present study are shown in Figure 1B.…”
Section: Functional Properties Water and Oil Absorption Capacity (Wacmentioning
confidence: 78%
See 1 more Smart Citation
“…Determining WAC is important as it assists in the formulation of various food products such as bread and soups (Oshodi and Adeladun, 1993;Bhat et al, 2008). Results obtained for the WAC and OAC for the different rice varieties evaluated in the present study are shown in Figure 1B.…”
Section: Functional Properties Water and Oil Absorption Capacity (Wacmentioning
confidence: 78%
“…Rice with acceptable foaming capacity possesses high potential to be incorporated in various baked products (e.g. rice cakes and bread) (Akubor et al, 2000;Bhat et al, 2008).…”
Section: Functional Properties Water and Oil Absorption Capacity (Wacmentioning
confidence: 99%
“…As shown in Figure 1, smooth surface was observed on the unmodified PGE surface. The formation of spindle-like gold nanostructures not only enlarges the surface area of the electrode, but also improves the electron transfer rate between the electrode surface and the bulk solution, which has been confirmed by the performance of GPGE in electrochemical investigation of [Fe(CN) 6 ] 3À/4À system. (Figure 2B).…”
Section: Morphological Characterization Of the Pge And Gpgementioning
confidence: 57%
“…Some researchers have treated the seeds with electron-beam to reduce the toxicity level [6]. The Zandu pharmaceutical manufactured HP-200, marketed as "Zandopa" which contains Mucuna pruriens seed powder and being used for the treatment of Parkinsons disease in India [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This was contrary to the result observed for WAC for cowpea protein isolate (1.89-2.15 mL/g) reported by Appiah et al [55], soy-isolate (289%) Kanu et al [56], but can be compared with the result of Wu et al [57] for groundnut protein isolate (135%). The observed variation in WAC among the cultivars of groundnut protein isolate may be attributed to the fact that water absorption capacity is a function of numerous parameters such as size, shape, steric factors, conformational characteristics, different protein concentration (hydrophilichydrophobic balance of amino acids in the protein molecules), as well as lipids, carbohydrate and tannins associated with proteins interaction with water [58]. Carbohydrates contain hydrophilic parts such as polar or charged side chains which can enhance WAC [59].…”
Section: Functional Properties Of γ-Irradiated Groundnut Protein Isolmentioning
confidence: 99%